2023
DOI: 10.3390/nu15061392
|View full text |Cite
|
Sign up to set email alerts
|

Soy Extract, Rich in Hydroxylated Isoflavones, Exhibits Antidiabetic Properties In Vitro and in Drosophila melanogaster In Vivo

Abstract: In the context of the growing prevalence of type 2 diabetes (T2DM), control of postprandial hyperglycemia is crucial for its prevention. Blood glucose levels are determined by various factors including carbohydrate hydrolyzing enzymes, the incretin system and glucose transporters. Furthermore, inflammatory markers are recognized predictors of diabetes outcome. Although there is some evidence that isoflavones may exhibit anti-diabetic properties, little is known about to what extent their corresponding hydroxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Drosophila insulin-like peptides (Dilp), whose release from insulin producing cells (IPC) in response to rising glucose levels is mediated by a Kir6.1/SUR1-dependent mechanism similar to that in mammalian β-cells, counteract hyperglycaemia. Accordingly, the fruit fly has been found to be a suitable in-vivo model that can be employed not only to study and decipher molecular mechanisms of glucose homeostasis and related metabolic dysfunctions ( Graham and Pick, 2017 ; Biglou et al, 2021 ; Chatterjee and Perrimon, 2021 ) but also to evaluate or verify modulating properties of plant extracts in this context ( Bai et al, 2018 ; Günther et al, 2021 ; Nakitto et al, 2021 ; Ollinger et al, 2022 ; Bauer et al, 2023 ; Lüersen et al, 2023 ; Omoboyowa et al, 2023 ). This is underlined by the fact that established oral hypoglycemic agents such as acarbose ( Günther et al, 2021 ), metformin ( Abrat et al, 2018 ) and glibenclamide ( Kréneisz et al, 2010 ) have also been found to be effective in D. melanogaster .…”
Section: Methodological Toolbox To Study Glucose Homeostasis Modulati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Drosophila insulin-like peptides (Dilp), whose release from insulin producing cells (IPC) in response to rising glucose levels is mediated by a Kir6.1/SUR1-dependent mechanism similar to that in mammalian β-cells, counteract hyperglycaemia. Accordingly, the fruit fly has been found to be a suitable in-vivo model that can be employed not only to study and decipher molecular mechanisms of glucose homeostasis and related metabolic dysfunctions ( Graham and Pick, 2017 ; Biglou et al, 2021 ; Chatterjee and Perrimon, 2021 ) but also to evaluate or verify modulating properties of plant extracts in this context ( Bai et al, 2018 ; Günther et al, 2021 ; Nakitto et al, 2021 ; Ollinger et al, 2022 ; Bauer et al, 2023 ; Lüersen et al, 2023 ; Omoboyowa et al, 2023 ). This is underlined by the fact that established oral hypoglycemic agents such as acarbose ( Günther et al, 2021 ), metformin ( Abrat et al, 2018 ) and glibenclamide ( Kréneisz et al, 2010 ) have also been found to be effective in D. melanogaster .…”
Section: Methodological Toolbox To Study Glucose Homeostasis Modulati...mentioning
confidence: 99%
“…Although the combination of Ussing chamber with Caco-2 cell culture has rarely been used to examine SGLT1-mediated glucose transport (Yin et al, 2014), recent publications show that this technique is excellent for studying the impact of extracts/ substances on this target (Günther et al, 2021;Bauer et al, 2023;Lüersen et al, 2023). A particularly important parameter might be Frontiers in Pharmacology frontiersin.org using the PD7 clone of the Caco-2 cell line (Mahraoui et al, 1994).…”
Section: Pitfalls and Limitations Of The In-vitro Assaysmentioning
confidence: 99%
“…Additionally, the modes of action of isoflavone extract were found to be significant inhibitors of sodium/glucose cotransporter 1 (SGLT1)-dependent glucose transport, causing a decrease in C-reactive protein (CRP) messenger RNA (mRNA) and secretion of protein levels in cultured Hep B3 hepatocytes. Thus, there is some evidence indicating antidiabetic mechanisms related to the intake of soy isoflavones [73].…”
Section: Mechanisms Of Plant-derived Metabolites On Prevention Of Chr...mentioning
confidence: 99%
“…Like other plant extracts, the quality and antioxidant potential of a soybean extract are dependent on both its source and method of extraction. Isoflavones are the polyphenols mostly found in soybean and are mainly made up of genistein, daidzein, and glycitein, and these are made more bioavailable by incorporating the hydroxyl group through fermentation by microorganisms [31,101,102]. In three different antioxidant assays (DPPH, FRAP, and ABTS), daidzein, glycitein, and genistein have shown the highest antioxidant capacity in human intestinal Caco-2 cells, out of the 12 major soybean isoflavones [9].…”
Section: Small Molecule Natural Productsmentioning
confidence: 99%